STUDY OF AUDITORY FUNCTION IN HYPERTENSION DISEASE - Boltaev Anvar Ismailovich (Scholar Express Journals, 2024)
Comprehensive audiometry was performed in 100 patients with hypertension. Threshold pure-tone audiometry was used, the phenomenon of accelerating the increase in volume was studied according to the differential threshold of sound intensity, and speech audiometry was used by air and bone conduction. The thresholds for undifferentiated speech, 50 and 100% speech intelligibility were determined. The examination revealed various degrees of increase in tonal hearing thresholds in 89% of patients, and impaired speech intelligibility in 78% of patients. The nature of the tonal and speech curves was characteristic of damage to sound perception. The degree of hearing impairment for sounds and speech depended on the stage of hypertension. Speech intelligibility by bone conduction in the majority of patients with stage 2 and 3 hypertension was worse than by air conduction.
Keywords: auditory function; cortical hearing loss; speech intelligibility